[Is computer navigation a useful tool in unicompartmental knee arthroplasty? A pilot cadaver study] - Aldinger, P; Gill, H; Schlegel, U; Schneider, M; Clauss, M; Goodfellow, J; Murray, D; Breusch, S (2005)
We conducted this pilot cadaver study to investigate whether the use of a navigation system during minimally invasive unicompartmental knee arthroplasty leads to more consistent results than the conventional hand-guided technique. We describe the accuracy of implant positioning in using standard instrumentation and computer navigation. Radiographic assessment showed that accurate component placement was achieved using both methods. These results were not statistically significant. The computer navigated femoral component placement without intramedullary (IM) rod was as accurate as the conventional method with IM rod. The study showed that computer navigation can produce accurate results even without an intramedullary rod. Image guidance can maintain the accuracy of the standard instrumentation and enhance 3D vision and the intraoperative orientation of the surgeon.